Analysis of Risk Factors for Acute First-Ever Ischemic Stroke in the Elderly Population of Eastern Liaoning Province: A Case-Control Study - Liu WT; Yang ZC; Wang XH; Yang YJ; Liu C; Yan HB; Zhang YN; Wang J; He H (International Journal of General Medicine, 2025)
Wen-Tao Liu,1 Zhi-Chao Yang,1 Xiao-Hui Wang,1 Yuan-Jiao Yang,1 Chen Liu,1 Han-Bing Yan,1 Ya-Nan Zhang,1 Jun Wang,1 Hui He1– 4 1Clinical Research Center, Liaoning Province Benxi Central Hospital, Benxi, Liaoning, 117000, People’s Republic of China; 2Department of Research and Development, Liaoning Province Benxi Clinical Bio-Bank, Benxi, Liaoning, 117000, People’s Republic of China; 3Training Department, China Medical University Benxi Central Hospital Postgraduate Training Workstation, Benxi, Liaoning, 117000, People’s Republic of China; 4Department of Research and Development, Shenyang Kati Health Consulting Co. LTD, Shenyang, Liaoning, 110101, People’s Republic of ChinaCorrespondence: Hui He, Clinical Research Center, Liaoning Province Benxi Central Hospital, China Benxi Central Hospital Taizihe New City Campus, 120, Weining Avenue, Mingshan District, Benxi, Liaoning Province, 117000, People’s Republic of China, Tel +86-18941435621, Email lnbxwxf@yeah.netPurpose: This study aimed to assess the risk factors for acute first-ever ischaemic stroke (IS) in the elderly population aged ≥ 60 years in the eastern part of Liaoning Province, China.Patients and Methods: This retrospective case-control study was derived from the Benxi Clinical Biobank and the Thrombotic Chronic Non-Communicable Disease Cohort Study in Natural Populations in Eastern Liaoning (ChiCTR2300074593). We collected cases of acute IS in the elderly population and selected the corresponding controls in a 1:1 ratio for inclusion in the study. Data collection included sociodemographics, clinical characteristics, and laboratory characteristics. We used IBM SPSS Statistics V26.0 for Windows for descriptive statistical analysis and conditional logistic regression analysis to determine risk factors for IS.Results: This study included 326 cases (163 pairs) of study subjects. The median age of the cases and controls was 65 years (62– 70). Both groups were predominantly 60– 69 years old in the age subgroups, 69.3% in the case group and 74.2% in the control group, with a p-value of 0.011; females in both groups accounted for 49.1% in the case group and 49.1% in the control group. Variables with P < 0.05 in the univariate analysis included current smoking, current alcohol consumption, fasting blood glucose, and hypertension. Variables statistically significant in the univariate analysis entered into the multivariate multifactorial analysis. The results showed that hypertension (OR, 1.977; 95% CI, 1.322– 2.956) and current alcohol consumption (OR, 1.549; 95% CI, 1.086– 2.210) were independent risk factors for acute first-ever IS in the elderly population aged ≥ 60 years.Conclusion: Hypertension and current alcohol consumption are major risk factors for IS in an elderly population in eastern Liaoning Province.Keywords: aged, risk factors, ischemic stroke, case-control studies